NiMn-based bimetal-organic framework nanosheets supported on multi-channel carbon fibers for efficient oxygen electrocatalysis - Cheng, Weiren (2021)
Developing noble-metal-free bifunctional oxygen electrocatalysts is of great significance for energy conversion and storage systems. Herein, we have developed a transformation method for growing NiMn-based bimetal-organic framework (NiMn-MOF) nanosheets on multi-channel carbon fibers (MCCF) as a bifunctional oxygen electrocatalyst. Owing to the desired components and architecture, the MCCF/NiMn-MOFs manifest comparable electrocatalytic performance towards oxygen reduction reaction (ORR) with the commercial Pt/C electrocatalyst and superior performance towards oxygen evolution reaction (OER) to the benchmark RuO2 electrocatalyst. X-ray absorption fine structure (XAFS) spectroscopy and density functional theory (DFT) calculations reveal that the strong synergetic effect of adjacent Ni and Mn nodes within MCCF/NiMn-MOFs effectively promotes the thermodynamic formation of key *O and *OOH intermediates over active NiO6 centers towards fast ORR and OER kinetics.